Comprehensive evaluation method for compressive property of coal mine grouting reinforcement material
Through a comprehensive evaluation method, including static and dynamic compression resistance performance evaluation, the problem of single evaluation methods in the prior art is solved, and the compressive performance and toughness of comprehensive reaction materials are ensured to select suitable materials in coal mine projects and improve safety Sex and efficiency.
Patent Information
- Application Number
- CN202411471650.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing chemical grouting reinforced materials have a single method to evaluate the compressive performance of chemical grouting reinforced materials, which cannot comprehensively evaluate the early, final and dynamic compressive performance of the material, and cannot reflect the toughness of the material, resulting in the material selected in actual engineering that does not meet the requirements, which may be Causes no reinforcement effect or safety hazards.
A comprehensive evaluation method for the compressive performance of coal mine grouting reinforcement materials is proposed, including static compressive performance evaluation and dynamic compressive performance evaluation. Static compression performance evaluation was carried out through uniaxial compression strength test under different aging times, dynamic compression performance evaluation was carried out through Hopkinson's press rods for dynamic impact performance testing, and the data was processed by two-wave method to draw the stress-strain curve. The evaluation was carried out by the evaluation. Toughness of the material.
This method can comprehensively and deeply reflect the compressive properties of materials, including static, dynamic, early and final strength, as well as toughness information, make up for the singularity of existing methods, provide a basis for material performance optimization and new material development, and Provides a scientific basis for the selection of grouting materials on the coal mine, and solves the safety hazards caused by the material performance not meeting actual needs.
Smart Images

Figure BDA0005095678690000031 
Figure BDA0005095678690000041 
Figure BDA0005095678690000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of grouting reinforcement of coal mine excavation working faces, and in particular, the invention relates to a comprehensive evaluation method for the compressive performance of coal mine grouting reinforcement materials. Background Art
[0002] With the continuous exploitation of coal resources, shallow coal resources on the earth have tended to be exhausted. At present, the average coal seam mining depth is about 600m, and shallow reserves exceeding one kilometer account for more than 53%. In addition, almost all central and eastern regions of my country have entered the deep mining stage. The high degree of fragmentation of the mining face in deep mines not only greatly reduces production efficiency, but also threatens the safety of underground workers and equipment. Therefore, it is imperative to solve the problem of safe and efficient mining of the fragmented mining face in deep mines.
[0003] At the current stage of development of materials and engineering practice in my country, advanced chemical grouting reinforcement has become a necessary means to prevent and control broken mining working faces. Filling and compaction is one of the most important mechanisms for achieving chemical grouting reinforcement. Therefore, the compressive strength of the slurry stone body is a very important strength indicator, which is directly related to the grouting reinforcement effect.
[0004] However, the current evaluation method for the compressive strength of chemical grouting reinforcement materials is relatively simple (industry standard AQ / T 1089-2020). AQ / T 1089-2020 "Polymer Materials for Coal Mine Reinforcement" stipulates that after the slurry solidifies for 3 days, a cylindrical specimen with a diameter of 50mm and a height of 100mm is prepared, and the compressive strength is measured by uniaxial compression using a press, and the compressive strength is required to be ≥40MPa. Therefore, the evaluation method for the compressive performance of chemical grouting reinforcement materials has only one indicator, namely the 3-day compressive strength. The compressive performance evaluation method has the following problems: 1) It cannot evaluate the early and final compressive performance: the material must be aged for 3 days before testing, and only the 3-day compressive strength can be known. The evaluation method of the early (such as 6h) and final compressive strength is unknown; 2) It cannot evaluate the dynamic impact performance: the working face that is greatly affected by mining will be subjected to impact pressure from time to time. If the dynamic impact strength of the reinforcement material is insufficient, it is difficult to meet the on-site needs; 3) It cannot evaluate the toughness of the material: the traditional method has only one uniaxial compressive strength index, which is difficult to reflect the toughness information of the material. When the pressure at both ends is large, better toughness is required, and the top plate remains intact after pressure; 4) More importantly, due to the single evaluation method, the materials selected in the grouting reinforcement project do not meet the actual needs. At the least, they cannot meet the reinforcement needs, and at the worst, they cause safety accidents, which violates the original intention of disaster management.
[0005] In fact, different mining faces in coal mines have different geological characteristics and different engineering environments, so the reinforcement needs are bound to be different. For example, when urgently reinforcing a fault, the slurry needs to have a higher early strength (greater than 30MPa in 6 hours); the working face that is greatly affected by mining needs the reinforcement material to have better impact strength; when the pressure at both ends is large, the material needs to have higher toughness; when reinforcing the coal pillar, a higher final strength is required, etc. Therefore, there is an urgent need for a comprehensive evaluation method for the compressive properties of coal mine grouting reinforcement materials, including static strength, dynamic strength, early strength, final strength and toughness. Summary of the invention
[0006] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, an embodiment of the present invention provides a comprehensive evaluation method for the compressive performance of coal mine grouting reinforcement materials.
[0007] The embodiment of the present invention provides a method for comprehensively evaluating the compressive performance of coal mine grouting reinforcement materials, comprising the following steps:
[0008] S1, static compressive performance evaluation:
[0009] The grouting liquid is poured into a test piece through a mold, and then the test piece is aged for different lengths of time in a standard environment and then subjected to a uniaxial compression strength test to obtain the compressive strength variation law of the test pieces at different aging ages, which is used to evaluate the static compressive performance of the test pieces;
[0010] S2, dynamic compressive performance evaluation:
[0011] S21, CNC machining the static compressive performance evaluation specimen;
[0012] S22, selecting qualified samples from the samples processed in step S21 and performing end surface processing;
[0013] S23, performing a dynamic impact performance test on the sample obtained in step S22 using a Hopkinson bar, and processing the obtained data using a two-wave method to obtain strain data, strain rate data, and stress data;
[0014] S24, based on the strain data, strain rate data and stress data obtained in step S23, a stress-strain curve is plotted to evaluate the dynamic compressive performance of the sample.
[0015] In some embodiments of the present invention, the step S23 further includes performing stress balance verification on the specimen after data processing, that is, stress balance is achieved at both end surfaces of the specimen under impact load.
[0016] In some embodiments of the present invention, in step S1, during the uniaxial compression strength test, when the compressive strength of the sample drops to 90% of the peak strength, the sample is considered to be damaged, the peak strength is recorded as static compressive strength, and the deformation of the sample when it reaches the peak strength is recorded as s%. The larger the s%, the better the toughness of the sample.
[0017] In some embodiments of the present invention, in step S21, the test piece is processed into a round cake with a diameter of 35-40 mm and a thickness of 8-10 mm.
[0018] In some embodiments of the present invention, in step S22, the qualified sample is a sample with no surface defects and two end surfaces that are parallel.
[0019] In some embodiments of the present invention, in step S22, the step of end surface treatment is: applying vaseline on both end surfaces of the qualified sample.
[0020] In some embodiments of the present invention, in step S23, the Hopkinson pressure bar is made of low carbon steel, and the elastic modulus of the low carbon steel is 180-200 GPa.
[0021] In some embodiments of the present invention, in step S23, the specific process of the dynamic impact performance test is: using a Hopkinson pressure bar to test the samples at different aging ages, and performing three parallel tests on the samples at each aging time, and performing mean processing on the obtained data.
[0022] In some embodiments of the present invention, in step S23, the formula used when processing data using the two-wave method is as follows:
[0023]
[0024] Where, ε(t) is the average strain; is the average strain rate; σ(t) is the average stress.
[0025] The advantages and beneficial effects of the embodiments of the present invention are as follows:
[0026] (1) The evaluation method of the embodiment of the present invention is relatively comprehensive, including two aspects: static compressive performance evaluation and dynamic compressive performance evaluation, and can reflect the early strength performance, mid-term strength performance and final strength performance, and also includes the toughness information of the sample, which makes up for the shortcoming of the current evaluation method being relatively single, and can provide a reference for the revision of safety standards.
[0027] (2) The evaluation method in the embodiment of the present invention can comprehensively and profoundly reflect the compressive performance of the material, and provide a basis for material performance optimization and new material development.
[0028] (3) The evaluation method in the embodiment of the present invention can provide a basis for the selection of grouting materials on site in coal mines, and solve the bottleneck problem of no reinforcement effect or even safety hazards caused by material properties not meeting actual requirements. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0030] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by those having ordinary skills in the field to which the present invention belongs.
[0031] Where values are described herein as a range, it should be understood that such disclosure includes disclosure of all possible sub-ranges within that range, as well as specific values falling within that range, regardless of whether a specific value or a specific sub-range is explicitly stated.
[0032] Herein, the words "comprises" and "includes" and variations thereof mean that other elements or integers which are permitted but not specifically described may be included.
[0033] The embodiment of the present invention provides a method for comprehensively evaluating the compressive performance of coal mine grouting reinforcement materials, comprising the following steps:
[0034] S1, static compressive performance evaluation:
[0035] The grouting liquid is poured into a test piece through a mold, and then the test piece is aged for different lengths of time in a standard environment and then subjected to a uniaxial compression strength test to obtain the compressive strength variation law of the test pieces at different aging ages, which is used to evaluate the static compressive performance of the test pieces;
[0036] S2, dynamic compressive performance evaluation:
[0037] S21, CNC machining the static compressive performance evaluation specimen;
[0038] S22, selecting qualified samples from the samples processed in step S21 and performing end surface processing;
[0039] S23, performing a dynamic impact performance test on the sample obtained in step S22 using a Hopkinson pressure bar (SHPB), and processing the obtained data using a two-wave method to obtain strain data, strain rate data, and stress data;
[0040] S24, based on the strain data, strain rate data and stress data obtained in step S23, a stress-strain curve is plotted (the peak strength in the stress-strain curve can reflect the toughness information of the sample) to evaluate the dynamic compressive performance of the sample.
[0041] In some specific embodiments, the step S23 further includes performing stress balance verification on the specimen after data processing to ensure the accuracy of the dynamic impact performance test results, that is, the stress balance is achieved at both end surfaces of the specimen under the impact load; that is, the incident wave σ1 and the reflected wave σ R The superposition wave (σ1+σ R ) and the transmitted wave σ T The overlap is good.
[0042] In some specific embodiments, in step S1, during the uniaxial compression strength test, when the compressive strength of the sample drops to 90% of the peak strength, the sample is considered to be damaged, the peak strength is recorded as static compressive strength, and the deformation of the sample when it reaches the peak strength is recorded as s%. The larger the s%, the better the toughness of the sample.
[0043] In some specific embodiments, in step S1, the standard environment refers to environmental conditions with a temperature of 23±2° C. and a relative humidity of 50±5%.
[0044] In some specific embodiments, in step S21, the test piece is processed into a round cake with a diameter of 35-40 mm and a thickness of 8-10 mm.
[0045] In some specific embodiments, in step S22, the qualified sample is a sample with no surface defects and two end surfaces that are parallel.
[0046] In some specific embodiments, in step S22, the step of end surface treatment is: applying vaseline on both end surfaces of the qualified sample to reduce the friction between the sample and the Hopkinson pressure bar, which is conducive to achieving stress balance.
[0047] In some specific embodiments, in step S23, the material of the Hopkinson pressure bar is low carbon steel, and the elastic modulus of the low carbon steel is 180-200 GPa.
[0048] In some specific embodiments, in step S23, the specific process of the dynamic impact performance test is: using a Hopkinson pressure bar to test the samples at different aging ages respectively, and performing three parallel tests on the samples at each aging time, and performing mean processing on the obtained data.
[0049] In some specific embodiments, in step S23, the formula used when processing data using the two-wave method is as follows:
[0050]
[0051] Where, ε(t) is the average strain; is the average strain rate; σ(t) is the average stress.
[0052] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments.
[0053] Example 1
[0054] This embodiment takes polyurethane grouting reinforcement material as an example to conduct a comprehensive evaluation of its compressive performance, including the following steps:
[0055] S1, static compressive performance evaluation:
[0056] The polyurethane grouting reinforcement material was poured into a mold to cast a cylindrical specimen with a diameter of 50 mm and a height of 100 mm. The cylindrical specimen was then aged in a standard environment at a temperature of 23°C and a relative humidity of 50%. The aging time was 6 h, 12 h, 36 h, 72 h, 120 h, and 240 h, respectively. After aging, the specimen was subjected to a uniaxial compression test. The test data are shown in Table 1:
[0057] Table 1
[0058] Aging time / h 6 12 36 72 120 240 Peak strength / MPa 5 13 19 25 36 38 Deformation / % 62 61 59 58 58 58
[0059] Static compressive evaluation: From the test results in Table 1, it can be seen that the early strength (within 12 hours) of the grouting reinforcement material is ≤13MPa, and the deformation is large (over 61%), indicating that the grouting reinforcement material is elastic, has good toughness and weak rigidity, and is therefore not suitable for reinforcement projects that require early strength and rigidity.
[0060] S2, dynamic compressive performance evaluation:
[0061] S21, the static compression test piece was processed into a round cake with a diameter of 35 mm and a thickness of 8 mm using a CNC machine tool;
[0062] S22, selecting qualified specimens with smooth surfaces and no defects and parallel end surfaces from the specimens processed in step S21, and applying a layer of vaseline on the end surfaces of the qualified specimens;
[0063] S23, the sample obtained in step S22 is subjected to a dynamic impact performance test using a Hopkinson pressure bar (SHPB, made of low carbon steel, with an elastic modulus of 180 GPa), that is: the dynamic impact performance test (impact velocity of 10 m / s) is performed on the samples with aging ages of 6h, 12h, 36h, 72h, 120h, and 240h, respectively, and the sample at each aging time is tested three times in parallel for average processing, and the obtained data is processed using a two-wave method to obtain strain data, strain rate data, and stress data;
[0064] S24, according to the strain data, strain rate data and stress data obtained in step S23, a stress-strain curve is plotted, and then the peak strength is read from the stress-strain curve. The results are shown in Table 2:
[0065] Table 2
[0066]
[0067] Dynamic compressive evaluation: From the test results in Table 2, it can be seen that the grouting reinforcement material has a relatively high peak strength (greater than 20MPa) in the early stage (within 12h) under dynamic impact, indicating that the sample has a certain toughness and can withstand impact without damage; with the extension of aging time, the peak strength of the sample gradually increases. Due to the increase in rigidity, the sample has obvious cracks, but it is still not damaged, indicating that the sample can still withstand external forces.
[0068] Example 2
[0069] This embodiment takes inorganic modified polyurethane grouting reinforcement material as an example to conduct a comprehensive evaluation of its compressive performance, including the following steps:
[0070] S1, static compressive performance evaluation:
[0071] The inorganic modified polyurethane grouting reinforcement material was poured into a mold to cast a cylindrical specimen with a diameter of 50 mm and a height of 100 mm. The cylindrical specimen was then aged in a standard environment at a temperature of 23°C and a relative humidity of 50%. The aging time was 6 h, 12 h, 36 h, 72 h, 120 h, and 240 h, respectively. After aging, the specimen was subjected to a uniaxial compression test. The test data are shown in Table 3:
[0072] Table 3
[0073] Aging time / h 6 12 36 72 120 240 Peak strength / MPa 30 35 41 42 42.5 43.7 Deformation / % 38 38 38 36 36 36
[0074] Static compressive evaluation: From the test results in Table 3, it can be seen that the early strength (within 12 hours) of the grouting reinforcement material is high, reaching 35MPa, and the deformation is small (38%), indicating that the grouting reinforcement material is relatively rigid and has a poor toughness, and is suitable for reinforcement projects that require early strength and rigidity.
[0075] S2, dynamic compressive performance evaluation:
[0076] S21, the static compression test piece was processed into a round cake with a diameter of 35 mm and a thickness of 8 mm using a CNC machine tool;
[0077] S22, selecting qualified specimens with smooth surfaces and no defects and parallel end surfaces from the specimens processed in step S21, and applying a layer of vaseline on the end surfaces of the qualified specimens;
[0078] S23, the sample obtained in step S22 is subjected to a dynamic impact performance test using a Hopkinson pressure bar (SHPB, made of low carbon steel, with an elastic modulus of 180 GPa), that is: the dynamic impact performance test (impact velocity of 10 m / s) is performed on the samples with aging ages of 6h, 12h, 36h, 72h, 120h, and 240h, respectively, and the sample at each aging time is tested three times in parallel for average processing, and the obtained data is processed using a two-wave method to obtain strain data, strain rate data, and stress data;
[0079] S24, according to the strain data, strain rate data and stress data obtained in step S23, a stress-strain curve is plotted, and then the peak strength is read from the stress-strain curve. The results are shown in Table 4:
[0080] Table 4
[0081]
[0082] Dynamic compressive evaluation: From the test results in Table 4, it can be seen that the grouting reinforcement material has a very high peak strength (48MPa) in the early stage (within 12h) under dynamic impact, indicating that the sample can withstand the impact without damage; with the extension of aging time, the peak strength of the sample gradually increases, and small cracks appear in the sample due to the increase in rigidity; until the aging time is extended to 120h, the sample is slightly damaged. Therefore, the grouting reinforcement material has very good impact resistance in the early stage of aging, but as the aging time increases, the impact resistance of the grouting reinforcement material decreases significantly, and even breaks.
[0083] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0084] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A comprehensive evaluation method for the compressive performance of coal mine grouting reinforcement materials, characterized in that: The steps include: S1, static compressive performance evaluation: The grouting liquid is poured into a test piece through a mold, and then the test piece is aged for different lengths of time in a standard environment and then subjected to a uniaxial compression strength test to obtain the compressive strength variation law of the test pieces at different aging ages, which is used to evaluate the static compressive performance of the test pieces; S2, dynamic compressive performance evaluation: S21, CNC machining the static compressive performance evaluation specimen; S22, selecting qualified samples from the samples processed in step S21 and performing end surface processing; S23, performing a dynamic impact performance test on the sample obtained in step S22 using a Hopkinson bar, and processing the obtained data using a two-wave method to obtain strain data, strain rate data, and stress data; S24, based on the strain data, strain rate data and stress data obtained in step S23, a stress-strain curve is plotted to evaluate the dynamic compressive performance of the sample.
2. The method for comprehensive evaluation of compressive properties of coal mine grouting reinforcement materials according to claim 1, characterized in that: The step S23 also includes performing stress balance verification on the specimen after data processing, that is, stress balance is achieved at both end surfaces of the specimen under impact load.
3. The method for comprehensive evaluation of compressive properties of coal mine grouting reinforcement materials according to claim 1, characterized in that: In the step S1, during the uniaxial compression strength test, when the compressive strength of the sample drops to 90% of the peak strength, the sample is considered to be damaged, the peak strength is recorded as the static compressive strength, and the deformation of the sample when it reaches the peak strength is recorded as s%, and the larger the s%, the better the toughness of the sample.
4. The method for comprehensive evaluation of compressive properties of coal mine grouting reinforcement materials according to claim 1, characterized in that: In the step S21, the test piece is processed into a round cake with a diameter of 35-40 mm and a thickness of 8-10 mm.
5. The method for comprehensive evaluation of compressive properties of coal mine grouting reinforcement materials according to claim 1, characterized in that: In step S22, the qualified sample is a sample with no surface defects and two end surfaces that are parallel.
6. The method for comprehensive evaluation of compressive properties of coal mine grouting reinforcement materials according to claim 1, characterized in that: In the step S22, the step of end surface treatment is: applying vaseline on both end surfaces of the qualified sample.
7. The method for comprehensive evaluation of compressive properties of coal mine grouting reinforcement materials according to claim 1, characterized in that: In the step S23, the material of the Hopkinson pressure bar is low carbon steel, and the elastic modulus of the low carbon steel is 180-200 GPa.
8. The method for comprehensive evaluation of compressive properties of coal mine grouting reinforcement materials according to claim 1, characterized in that: In step S23, the specific process of the dynamic impact performance test is: using the Hopkinson pressure bar to test the samples at different aging ages respectively, and performing three parallel tests on the samples at each aging time, and performing mean processing on the obtained data.
9. The method for comprehensive evaluation of compressive properties of coal mine grouting reinforcement materials according to claim 1, characterized in that: In step S23, the formula used when processing data using the two-wave method is as follows: Where, ε(t) is the average strain; is the average strain rate; σ(t) is the average stress.
Citation Information
Cited By
Method for evaluating plugging pressure-bearing performance of temperature-sensitive adhesive plugging material for deep fractured formation
CN120102291A
Method for evaluating residual service performance and toughness of tunnel grouting reinforced surrounding rock
CN121683284A
A method for evaluating the residual service performance and toughness of tunnel grouting reinforced surrounding rock
CN121683284B